Parâmetros clínicos e laboratoriais da resposta imune em equinos submetidos à auto-hemoterapia - Paula Rodrigues Lopes (2018)
Autohemotherapy (AHT) consists of the application of autologous blood intramuscularly or subcutaneously in order to stimulate the immune system. It is an old technique with reports all over the world, but with little scientific background making its use and function questionable. Its results and clinical experiences indicate an immunological increase due to the improvement observed in patients with chronic, autoimmune and post-surgical preventive diseases. Although little scientifically proven, AHT and its byproducts are believed to increase the migration of leukocytes to the organs, increasing their organic activity, an increase in the peripheral circulation of monocytes and increased production of macrophages, thus becoming an active therapy the Monocytic Phagocytic System. From the different hypotheses about the technique, this study proposed to characterize the immunological aspects of AHT in horses. To do this, eight healthy animals were submitted to three sessions of AHT with intervals of seven days with blood volume applied in the muscle according to the weight of each animal following the protocol of 20mL per 100kg of live weight. Cellular and molecular aspects of the peripheral blood of horses submitted to AHT were evaluated before (T0) and three days (T1, T2 and T3) after each application of AHT including clinical, biochemical and hematological parameters, evaluation of the phenotypic profile of T lymphocytes (CD3) and B (CD21), the evaluation of intracytoplasmic cytokines (IFN-, IL-4, IL-6, IL-8 and IL-10) and finally the phagocytic activity of anti-Zymosan neutrophils. Our results demonstrated a lack of local or systemic reaction in the animals after AHT application. An increase in the T lymphocyte (CD3) population was observed in the first weeks of application (T1 and T2) and, in turn, a decrease in the B cell population (CD21) in the three times. Increased production of cytokine IFN- and IL- 10 was observed in the three post-AHT times with a consequent decrease in IL-6 and IL-8 cytokines. Finally, the phagocytic activity of anti-Zimosan neutrophils showed no change during the study. In summary the results showed that AHT did not alter the clinical and hematological parameters of the animals; a small change in the status of the immune response was observed, leading to a more inflammatory initial response followed by a regulatory response, tending to a balance. Considering the results, studies using new immunological markers should be carried out in order to bring more subsidies that can confirm that AHT is a technique with scientifically feasible results.